Designing fuzzy backstepping adaptive based fuzzy estimator variable structure control: applied to internal combustion engine - Nekooei, M. J. (2013)
The method of assessing the insulation condition in high voltage (HV) electrical equipments can never be overemphasized. Over the years, several method of assessing the insulation condition have been researched & used by many researchers. One of these methods is using the dielectric response of the materials to determine the Polarization and Depolarization Current (PDC). PDC is a non-destructive assessment method that combines a sequence of switching operations & current measurement for time domain response. In this paper, the HV switching sequence for a PDC assessment was designed & built to fulfill the PDC assessment basic theory. The switch was applied on three materials used in HV insulation to determine their polarization current (ip) & depolarization current (id). Test duration for both ip & id were 10000 seconds and the test results are presented as a current pattern. The current pattern is consistent with the theoretical current wave PDC pattern from literatures thereby confirming the validity of the built switching device.